2016
DOI: 10.1016/j.apacoust.2016.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Identification of vehicle suspension shock absorber squeak and rattle noise based on wavelet packet transforms and a genetic algorithm-support vector machine

Abstract: Squeak and rattle (S&R) Wavelet packet transform (WPT) Wavelet packet energy (WPE) Wavelet packet sample entropy (WPSE) Genetic algorithm (GA) Support vector machine (SVM) a b s t r a c tThe squeak and rattle (S&R) noise of a vehicle's suspension shock absorber substantially influences the psychological and physiological perception of passengers. In this paper, a state-of-the-art method, specifically, a genetic algorithm-optimized support vector machine (GA-SVM), which can select the most effective feature sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(9 citation statements)
references
References 32 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…The SVM model with RBF had a higher R 2 and a lower mean squared error (MSE) for the validation dataset than that with PKF, which indicated a better agreement between the predicted TRIX values and the measured TRIX values. Recent works also suggested that the use of RBF in the SVM regression model was appropriate and sufficient because of its effectiveness, robustness, the acceptable generalization ability and the promising results (Chou et al, 2014;Sajan et al, 2015;Huang et al, 2016;Mehraein and Riahi, 2017 …”
Section: Model Development and Performance Evaluationmentioning
confidence: 98%
“…The SVM model with RBF had a higher R 2 and a lower mean squared error (MSE) for the validation dataset than that with PKF, which indicated a better agreement between the predicted TRIX values and the measured TRIX values. Recent works also suggested that the use of RBF in the SVM regression model was appropriate and sufficient because of its effectiveness, robustness, the acceptable generalization ability and the promising results (Chou et al, 2014;Sajan et al, 2015;Huang et al, 2016;Mehraein and Riahi, 2017 …”
Section: Model Development and Performance Evaluationmentioning
confidence: 98%
“…It is generally considered that a typical four-stroke engine has a stroke period of 80 ms under idle condition with rotation speed 1500 rpm in the vehicle system [28]. When the engine is disturbed by internal and external factor, the angular velocity and angular acceleration of active gears on the input shaft of the gear transmission system will uctuate that are shown in Figure 3.…”
Section: Nonlinear Rattle Dynamicsmentioning
confidence: 99%
“…Because of road bumps, engine operation, and vibration of components such as suspension and transmission systems, excitations from different sources are transmitted to the vehicle body panel through the suspension point in the driver's cab and eventually lead to noise emission [3,4]. In addition, sound waves exert a force on the panel in the driver's cab, causing the cab to vibrate and generate radiated noise [5]. Cab noise is an important performance indicator for agricultural machines, and it depends on the vibration source of the machine, transmission path of vibration, and dynamic characteristics of the cab itself.…”
Section: Introductionmentioning
confidence: 99%